Light-Activated Chemical Probing of Nucleobase Solvent Accessibility Inside Cells - Feng, Chao (Nat Chem Biol, 2018)
The discovery of functional RNAs critical for normal and disease physiology continues to expand at a break-neck pace. Many RNA functions are controlled by the formation of specific structures; an understanding of each structural component is necessary to elucidate its function. Measuring solvent accessibility intracellularly with experimental ease is an unmet need in the field. Here, we present a novel method for probing nucleobase solvent accessibility, Light Activated Structural Examination of RNA (LASER). LASER depends on light activation of a small molecule, nicotinoyl azide (NAz), to measure solvent accessibility of purine nucleobases. In vitro, this technique accurately monitors solvent accessibility and identifies rapid structural changes due to ligand binding in a metabolite-responsive RNA. LASER probing can further identify cellular RNA-protein interactions and unique intracellular RNA structures. Our photo-activation technique provides an adaptable framework to structurally characterize solvent accessibility of RNA in a myriad of environments.